Pendampingan Pabrikasi Media Pembelajaran Komprehensif dalam Meningkatkan Kompetensi Pedagogik Guru SDN Tanjung Kabupaten Kediri - Pratiwi, Emy Yunita Rahma; Dwinata, Anggara; Nuruddin, Muhammad; Raharja, Hawwin Fitra; Susilo, Claudya Zahrani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Fabrication of learning media is an effort in the process of designing and producing learning media comprehensively. The comprehensive level consists of the levels of important subjects taught in elementary schools which include Natural Sciences, Social Sciences, Mathematics, Civics, and Indonesian. The aim of this activity is to help teachers in assisting in creating media so that they are skilled in designing and using it. This activity was carried out at SDN Tanjung, Kediri Regency with the target objects being the teachers at the school consisting of 16 people. The stages of this activity consist of partner situation analysis, literature review and material preparation, socialization, design and production, and use of media by teachers in the classroom. The results of this activity are that teachers feel very helped and happy with the fabrication of learning media as a form of improving teacher pedagogy in teaching students at school.